Leucaena in East Africa - Otsyina, R.; Hanson, Jean; Akyeampong, E. (Australian Centre for International Agricultural Research, 1995)
The East African highlands face servere erosion problems, declining soil fertility and acute shortages of fodder and fuelwood. These problems are worsened by the region's rapid population growth, but may be reduced if leguminous trees are integrated into the farming systems. Adapted leucaena species and provenances have the potential to control erosion and conserve soil on sloping lands, to improve soil fertility and to supply quality fodder and wood products. Wide use of leucaena in the highlands of eastern Africa has been limited by poor adaptation of Leucaena leucocephala to the highly acidic, aluminium rich soils and the high altitutdes. L. diversifolia provenances have shown tolerance to acidity, and recorded biomass yields comparable to the adapted tree, Calliandra calothyrsus. Use of L. diversifolia as green mulch and fodder has also shown very promising results. This paper outlines the potential for leucaena Development in the East African highlands (rainfall > 1000 mm, altitutde 1500-2900 m.a.s.l), and discusses priorities for Leucaena research in the zone.